Factors Affecting Overnutrition and Obesity Status in MI Khoirul Huda Students - Wihda Intan (CV, Akira Java Bulu, 2025)
The shift to online learning from home due to the Covid-19 pandemic has caused children to spend more time indoors, which can impact their behavior and lifestyle. This includes a decrease in physical activity, an increase in sedentary behavior, more screen time, and a decline in the quality of food consumed. These factors can lead to an increased incidence of overweight and obesity in children during the pandemic, with potential long-term effects on their health. This study aims to explore the relationship between factors such as age, gender, parents' occupation, frequency of fast food consumption, sugary drinks, snacks, screen media usage, and physical activity with overweight and obesity status among students of MI Khoirul Huda in Tangerang City in 2021. The study used a cross-sectional design, with 155 participants aged 6-14 years. The prevalence of overweight and obesity among these students was 29%. Most respondents were aged 10 years or older (53.5%), 50.3% were female, and 49.7% were male. A majority of the respondents had fathers with formal employment (74.2%) and mothers with informal employment (66.5%). Bivariate analysis using the chi-square test revealed no significant relationship between gender, parents' occupation, frequency of fast food consumption, sugary drinks, snacks, and physical activity with overweight and obesity status (P-value > 0.05). However, significant relationships were found between age (P-value 0.023; OR 2.470; CI 95% 1.186 - 5.144) and the duration of screen media use per week (P-value 0.034; OR 2.516; CI 95% 1.132 - 5.590) with overweight and obesity status. The study recommends paying more attention to children's food intake and physical activity to prevent overweight or obesity.